2016
DOI: 10.1111/tra.12452
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a caveolin‐1 mutation associated with both pulmonary arterial hypertension and congenital generalized lipodystrophy

Abstract: Congenital generalized lipodystrophy (CGL) and pulmonary arterial hypertension (PAH) have recently been associated with mutations in the caveolin-1 (CAV1) gene, which encodes the primary structural protein of caveolae. However, little is currently known about how these CAV1 mutations impact caveolae formation or contribute to the development of disease. Here, we identify a heterozygous F160X CAV1 mutation predicted to generate a C-terminally truncated mutant protein in a patient with both PAH and CGL using who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 55 publications
3
69
0
Order By: Relevance
“…We previously reported both mutants are capable of generating 8S complexes when expressed either individually or in combination with WT CAV1 (22,25). Interestingly, the complexes containing F160X are destabilized compared to those formed by WT CAV1 (22). Our current findings suggest this destabilization is the direct result of disruption of the central stalk together with packing defects of the protein in the center of the 8S complex resulting from the loss of residues 160-178 due to the frameshift.…”
Section: Proposed Model For How 8s Complexes Assemble and How Defectsmentioning
confidence: 46%
See 1 more Smart Citation
“…We previously reported both mutants are capable of generating 8S complexes when expressed either individually or in combination with WT CAV1 (22,25). Interestingly, the complexes containing F160X are destabilized compared to those formed by WT CAV1 (22). Our current findings suggest this destabilization is the direct result of disruption of the central stalk together with packing defects of the protein in the center of the 8S complex resulting from the loss of residues 160-178 due to the frameshift.…”
Section: Proposed Model For How 8s Complexes Assemble and How Defectsmentioning
confidence: 46%
“…Our results also shed light on how the human CAV1 mutations F160X and P158P contribute to disease. We previously reported both mutants are capable of generating 8S complexes when expressed either individually or in combination with WT CAV1 (22,25). Interestingly, the complexes containing F160X are destabilized compared to those formed by WT CAV1 (22).…”
Section: Proposed Model For How 8s Complexes Assemble and How Defectsmentioning
confidence: 96%
“…Aggresome formation could also potentially be triggered when endogenous Cav1 is either overexpressed or mutated, a possibility that merits further study. This is especially important given the growing number of Cav1 mutations associated with human disease43444546. Finally, our results indicate that conditions that favor aggresome formation, such as proteasome inhibition, can lead to the trapping of endogenous wild type Cav1 in aggresomes.…”
Section: Discussionmentioning
confidence: 65%
“…This could potentially impact whether the fluorescent proteins can interact with one another, or otherwise disrupt to folding or oligomerization of Cav1. In this regard, it is interesting to note that several studies have shown the C-terminus of Cav1 is important for oligomerization4142 and mutations in the C-terminus of Cav1 are associated with human diseases43444546. Taken together, these findings suggest that the C-terminus of Cav1 is especially sensitive to manipulation.…”
Section: Discussionmentioning
confidence: 88%
“…Biallelic variants in eukaryotic initiation translation factor (EIF2AK4) cause pulmonary veno-occlusive disease (PVOD) and pulmonary capillary hemangiomatosis (PCH) (20,21). Loss of function variants in channelopathy genes potassium two pore domain channel (KCNK3) (22) and ATP-binding cassette subfamily member 8 (ABCC8) (23), as well as membrane reservoir gene caveolin-1 (CAV1) (24)(25)(26), are causative for PAH. Recent associations of variants in ATPase 13A3 (ATP13A3) and aquaporin 1 (AQP1) (7), as well as kallikrein 1 (KLK1) and gamma-glutamyl carboxylase (GGCX) (6) have been recently reported but require independent confirmation.…”
mentioning
confidence: 99%